FORMATION OF CORRUPTION ERADICATION COMISSION - I Made Hendra Kusuma (Kertha Wicaksana, 2018)
Since the establishment of the Corruption Eradication Commission (KPK) in 2002, corruption eradication agency in Indonesia is authorized to a three sections), namely police agency, prosecutor’s office and KPK. Among the three institutions, the KPK has an extraordinary authority, which is not granted to the police agency or the prosecutor's office by the legislators. The authority includes the authority to take over the investigation of criminal act of corruption being perpetrated by the police officers or the prosecutors. In time police institution or prosecutor's office begins a graft investigation of a criminal act of corruption, it shall be reported to KPK within a period of time no later than 14 working days and shall continuously be coordinated with the KPK. Even if at the same time the police, prosecutors, and KPK are investigating the same corruption, the involvement of the police or the prosecutors must be discontinued immediately. With regard to this fact, this paper reviews descriptively what and how exactly KPK with its extraordinary authority was originally formed. This paper uses secondary data in the form of literature and minutes of the meeting on the establishment of law on KPK in the House of Representatives of the Republic of Indonesia (DPR-RI). The result of the study shows that the establishment of the KPK according to Law No. 30 of 2002 was designed to form an independent and super-agency of corruption eradication, with some authorities previously never granted to the police or the prosecutors, but by not eliminating the authority of the police and prosecutors as a part of corruption eradication institutions that have been already existed. In such a position, KPK functioned as a trigger mechanism holder over the police and prosecutors who are considered do not effectively and efficiently execute the action of eradication on corruption.